Matrix Metalloproteinase-Responsive Mesoporous Silica Nanoparticles Cloaked with Cleavable Protein for “Self-Actuating” On-Demand Controlled Drug Delivery for Cancer Therapy - Vaghasiya, Kalpesh; Ray, Eupa; Sharma, Ankur; Katare, Om Prakash; Verma, Rahul Kumar (ACS applied bio materials, 2020)
The tumour site-specific stimulus responsiveness of smart drug delivery systems gives a unique system for effective therapeutic delivery with reduced toxic effects of conventional chemotherapeutic drugs. In this work, matrix metalloproteinase-2 (MMP-2)-responsive mesoporous silica nanoparticles (MSNs) were synthesized and assessed for “self-actuating” on-demand controlled drug delivery for cancer therapy. MMPs are members of protease enzymes that are generally overexpressed in cancerous tissues in all stages of cancer. MSNs have attracted significant consideration as a potential delivery system because of their robust and versatile physicochemical properties suitable to deliver the therapeutic payload. Cisplatin (Cis) was used as a model drug, which was incorporated into MSNs to evaluate targeting of lung cancer cells and their release kinetics. In this delivery system, collagen was coated on the surface of Cis-loaded MSNs (Cis-MSN) to form a capping layer, resulting in collagen-coated MSNs (Cis-col-MSN). Under normal cell conditions, a collagen-capping coat efficiently forbids the release of Cis molecules from Cis-col-MSN. The tumor microenvironment would lead to augmented drug release because of the uncapping of collagen from MSN pores due to the presence of overexpressed MMP-2 enzyme and the ensuing controlled drug release. MMP-responsive experiments have shown augmented enzyme triggered drug release. The cellular uptake and cytocompatibility studies in A549 adenocarcinomic lung cancer cell lines demonstrated that this nanocarrier could be efficiently endocytosed in 24 h and have shown favorable biocompatibility with the cells. Cytotoxicity results of Cis-col-MSN demonstrated dose-dependent toxicity. The efficacy of the Cis-col-MSN significantly enhanced with the supplementation of MMP-2 enzyme with increasing concentrations in the cell culture milieu. The efficacy of formulation was attributed to significantly enhance reactive oxygen species, cell cycle arrest, and apoptosis. It is expected that Cis-col-MSN promises a pragmatic approach to constructing an “on-demand” smart drug delivery system to deliver a therapeutic payload at the tumor site only.